A note on weak convergence in Hilbert spaces - Ferreira, M. A. M.; Andrade, M.; Filipe, J. A. (International Journal of Academic Research, 2013)
In the Hilbert spaces domain, it is discussed in this work under which conditions weak convergence implies convergence.